AIM and ELF bonding analyses of M-O and M-N (Metal= Ba, Y, Zr) in metal-complexes using DFT approach / Nor Ain Fathihah Abdullah, Sharizal Hasan and Lee Sin Ang - Abdullah, Nor Ain Fathihah; Hasan, Sharizal; Lee, Sin Ang (Faculty of Applied Sciences, 2021)
The molecular interaction between the chelating agents of citric acid (CA), ethylenediaminetetraacetic acid (EDTA), and triethylenetetraamine (TETA) with metals (M = Ba, Y, and Zr) were studied using Density Functional Theory (DFT) method. This study aims to determine the type of bonding between M-O/N bonds in the CA/EDTA/TETA- complexes. In this study, each metal was attached at strategic positions of chelating agents and was optimized at B3LYP/6-31G* and UGBS level of theory. The M-O bonds were characterized based on Atoms- in-molecules (AIM) and Electron Localization Function (ELF) in the topological analysis. In AIM analysis, the total electron energy density at the bond critical point (BCP) of the M-O/N bonds are used to estimate the interaction involved. The low values of ρ(r) and positive values of ∇ 2 ρ(r) indicates that ionic character exists in the M-O/N bonds. In ELF color-filled map, the blue shaded region between M-O/N atom acts as an indicator for the existence of the ionic interaction. Both AIM and ELF results confirm the existence of ionic bonding between M-O/N bonds, with values of ρ(r) and ∇ 2 ρ(r) ranging from 0.02 to 0.12 au and 0.09 to 0.5 au respectively. Further analysis on charge distribution at M-O/N bonds show that the opposite charge between Ba, Y, and Zr with O/N assured the M- O/N ionic bonding interactions